Videos Improve Patient Understanding of Misunderstood Chemotherapy Terminology - Pentz, Rebecca D. (Cancer, 2019)
BACKGROUND: Chemotherapy is the backbone of many cancer therapies; however, the terminology used to describe chemotherapy may be difficult for patients to understand, particularly in underserved populations. Studies have shown that educational videos can improve patient understanding of cancer-related terms. The goal of this study was to identify chemotherapy terms that were difficult for an underserved population to understand and then develop and test educational videos describing these terms. METHODS: A word bank of 50 difficult-to-understand chemotherapy terms was developed by querying 15 providers and 50 patients at an underserved hospital. Twenty of these terms were then tested with 50 additional patients to determine rates of misunderstanding. Six pilot educational videos describing 6 important terms were created using VideoScribe and then assessed with 50 patients to see if they improved understanding. RESULTS: Fifteen of the 20 terms tested to establish rates of misunderstanding were misunderstood by more than one third of patients, with 98% unable to define maintenance, 74% unable to define cancer, and 58% unable to define chemotherapy. Patient understanding of all 6 terms improved by at least 20% after watching the videos. Notable improvement was reported for palliative chemotherapy, where before-and-after video understanding increased from 0% to 72%. CONCLUSION: Chemotherapy, a backbone of cancer treatment, is described with terms that are difficult to understand. Short, animated educational videos can significantly increase patient understanding of chemotherapy terminology.